Standardization of Shari'ah Compliance Establishment and Operation of Sharia Cooperatives in Indonesia - Abdurrahman Azmi (Jurnal Ilmiah Ekonomi Islam, 2023)
Sharia cooperatives have had many positive impacts on micro-businesses, and in a short time have been able to help around 920 thousand micro businesses in Indonesia. However, because there are still big problems in running sharia cooperatives, namely human resources that are not yet professional, sharia cooperatives need close supervision by those who understand sharia principles. One element of assessing the soundness of sharia cooperatives is compliance. adhere to sharia principles and always pay attention to the fatwas of the National Sharia Council (DSN). Given the many problems related to operations in sharia cooperatives, the researcher considers that discussion regarding the standardization of the establishment and operation of sharia cooperatives is very much needed. to be a benchmark for the level of sharia compliance in its operations. Therefore this research will examine the standardization of the establishment and operation of sharia cooperatives as analyzed from the DSN-MUI fatwa No.141/DSN-MUI/VII/2021 concerning guidelines for the establishment and operation of sharia cooperatives in Indonesia. The method used in this study is the descriptive qualitative method, through a literature survey which is then analyzed based on data sources. The results of this study are that the DSN-MUI fatwa no 141/DSN-MUI/VIII/2021 concerning guidelines for the establishment and operation of sharia cooperatives, has explained standardization, as well as sharia limitations on the establishment and operation of sharia cooperatives in Indonesia.